Anorectal Manometry Results of Patients Presenting with Chronic Constipation: Single-Center Outcomes - Gözde Derviş Hakim; Sevil Özer Sarı; Taner Kara; Venüs Tekoğlu (Diagnostic and Interventional Endoscopy)
Objective: Anorectal manometry serves as a diagnostic tool, particularly in identifying chronic constipation associated with rectal evacuation disorders. We aimed to share the anal motility results of patients presenting with constipation complaints in our tertiary referral center’s motility laboratory.